The production of reduced-alcohol wines using Gluzyme Mono® 10.000 BG-treated grape juice - Biyela, B.N.E.; du Toit, W.J.; Divol, B.; Malherbe, D.F.; van Rensburg, P. (South African Journal of Enology and Viticulture, 2016)
High alcohol wines have become a major challenge in the international wine trade. Several physical processes are used to produce wines with reduced-alcohol content, all of which involve the selective extraction of ethanol based on volatility or diffusion. In this study, the possibility of Gluzyme Mono® 10.000 BG (Gluzyme) (Novozymes, South Africa) to reduce the glucose content of synthetic grape juice before fermentation was investigated in order to produce wine with reduced-alcohol content. Gluzyme is a glucose oxidase preparation from Aspergillus oryzae, currently used in the baking industry. Glucose oxidase catalyses the oxidation of glucose to gluconic acid and hydrogen peroxide (H2O2) in the presence of molecular oxygen. Gluzyme was initially used in synthetic grape juice, where different enzyme concentrations and factors influencing its efficiency were investigated under winemaking conditions. The results showed up to 0.5% v/v less alcohol at an enzyme concentration of 20 kU compared to the control samples. This reduction in alcohol was increased to 1 and 1.3% v/v alcohol at pH 3.5 and pH 5.5 respectively in aerated (8 mg/L O2) synthetic grape juice using 30 kU enzyme. Secondly, Gluzyme was used to treat Pinotage grape must before fermentation. Gluzyme-treated wines at 30 kU enzyme concentration after fermentation contained 0.68% v/v less alcohol than the control wines. A decrease in acetic acid concentration of the treated compared to control wines was also observed.